Sciadonic acid attenuates high-fat diet-induced obesity in mice with alterations in the gut microbiota - Chen, Lin; Jiang, Qihong; Jiang, Chenkai; Lu, Hongling; Hu, Wenjun; Yu, Shaofang; Li, Mingqian; Tan, Chin Ping; Feng, Yongcai; Xiang, Xingwei; Shen, Guoxin (Royal Society of Chemistry (RSC), 2023)
Obesity has been reported to be associated with dysbiosis of gut microbiota. Sciadonic acid (SC) is one of the main functional components of Torreya grandis “Merrillii” seed oil. However, the effect of SC on high-fat diet (HFD)-induced obesity has not been elucidated. In this study, we evaluated the effects of SC on lipid metabolism and the gut flora in mice fed with a high-fat diet. The results revealed that SC activates the PPARα/SREBP-1C/FAS signaling pathway and reduces the levels of total cholesterol (TC), triacylglycerols (TG), and low-density lipoprotein cholesterol (LDL-C), but increases the level of high-density lipoprotein cholesterol (HDL-C) and inhibits weight gain. Among them, high-dose SC was the most effective; the TC, TG and LDL-C levels were reduced by 20.03%, 28.40% and 22.07%, respectively; the HDL-C level was increased by 8.55%. In addition, SC significantly increased glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) levels by 98.21% and 35.17%, respectively, decreased oxidative stress, and ameliorated the pathological damage to the liver caused by a high-fat diet. Furthermore, SC treatment altered the composition of the intestinal flora, promoting the relative abundance of beneficial bacteria such as Lactobacillus and Bifidobacterium, while simultaneously decreasing the relative abundance of potentially harmful bacteria such as Faecalibaculum, norank_f_Desulfovibrionaceae, and Romboutsia. Spearman's correlation analysis indicated that the gut microbiota was associated with SCFAs and biochemical indicators. In summary, our results suggested that SC can improve lipid metabolism disorders and regulate the gut microbial structure.